The “Thrice- An Angelic Liturgical Formula in Jewish and Christian Traditions - Stone, E. Michael (Mesrop Mashtots Institute of Ancient Manuscripts)
In an Armenian parabiblical text dealing with events that traditionally took place from the Fall of the Angels before the Creation, and down to Moses and the Exodus (“Questionnaire”), one passage quotes Isa 6:3b as the praise pronounced by the Seraphs, the second of the nine angelic classes. The present article traces aspects of the varied development of this Isaianic formula in Armenian and other Christian traditions as well as in Jewish sources, up until its appearance in Questionnaire. This review reveals a complex interweaving of ideas about the celestial liturgy, angelology, numerology, and human liturgy, which have all been associated with the Isaianic formula. The ramifications of this biblical expression of unclear origin have immense implications.
Keywords: Philology